Pengaruh Teknik Brainstorming Terhadap Komunikasi Interpersonal Siswa Kelas VIII di UPTD SMP Negeri 1 Gunungsitoli Utara - Wulan Harahap; Elizama Zebua; Hosianna Rodearni Damanik (Indo-MathEdu Intellectuals Journal, 2023)
One of the factors that favor individuals to successfully adapt to their environment is communication. The purpose of this study was to determine the effect of brainstorming techniques on students' interpersonal communication skills and how effective brainstorming techniques are in improving interpersonal communication of grade VIII students at UPTD SMP Negeri 1 Gunungsitoli Utara. This study used a type of quantitative-experimental research with a pretest-postest one group design. The data collection method uses tests and observation guidelines. The results showed that the pre-test scores of 10 students in grade VIII-E were in the low assessment range with an average score below 20. After being treated with brainstorming techniques, there was an increase in interpersonal communication skills as evidenced by obtaining an average student post test score above 30. The observation results show it is in the range of 75%. The calculation of the difference between O1-O2 is 47.2% which is in the range of 21-35 values, which is quite increased and the calculation of N-Gain which combines statistical results and observations before and after treatment by 62% with the category is quite effective. Based on the results of data analysis, it was concluded that brainstorming techniques were quite influential and effective in improving students' interpersonal communication skills